2016
DOI: 10.1039/c6ib00084c
|View full text |Cite
|
Sign up to set email alerts
|

Matrix stiffness exerts biphasic control over monocyte–endothelial adhesion via Rho-mediated ICAM-1 clustering

Abstract: Leukocyte-endothelial adhesion is a critical early step in chronic vascular inflammation associated with diabetes, emphysema, and aging. Importantly, these conditions are also marked by abnormal subendothelial matrix crosslinking (stiffness). Yet, whether and how abnormal matrix stiffness contributes to leukocyte-endothelial adhesion remains poorly understood. Using a co-culture of human monocytic cells and human microvascular endothelial cells (ECs) grown on matrices of tunable stiffness, we demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…These genes regulated or participated in cytoskeleton assembly, which is an important process for the formation of stress fibers and cell spreading. 34 37 As shown in Fig. 4A , the expression level of cytoskeleton-related genes (ACTB, PFN1 and CFL1) on the soft matrix presented a significant reduction compared to the stiff matrix, indicating a lower efficiency or depletion in number to produce stress fibers, because these genes participated in cytoskeleton assembly.…”
Section: Resultsmentioning
confidence: 96%
“…These genes regulated or participated in cytoskeleton assembly, which is an important process for the formation of stress fibers and cell spreading. 34 37 As shown in Fig. 4A , the expression level of cytoskeleton-related genes (ACTB, PFN1 and CFL1) on the soft matrix presented a significant reduction compared to the stiff matrix, indicating a lower efficiency or depletion in number to produce stress fibers, because these genes participated in cytoskeleton assembly.…”
Section: Resultsmentioning
confidence: 96%
“…It has been reported that cytoskeleton mediated the clustering of VCAM1 and ICAM1 [30], so it may also be an important signaling transduction from the stiffness of the substrate to various ECs responses. In addition, ion channels located on the plasma membrane have been reported to react to the mechanical stimulation rapidly within microseconds, which was also involved in the intracellular signaling [31] [32], thus participating in many physiological activities of cells like inflammatory responses and AJs integrity.…”
Section: Discussionmentioning
confidence: 99%
“…To unravel the molecular mechanism of this signaling pathway, the C-type lectin-related protein RCab, as the specific trigger of this signaling axis in ECs, was studied in vitro. RCab increased 1) mechanical tension between and within ECs, resulting in increased permeability of the vasculature, and 2) TEM of leukocytes at vascular sites of inflammation (9,20,43). Both processes are highly relevant in inflammatory diseases such as atherosclerosis and the life-threating SIRS (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…To fulfill their functions, ICAM-1 molecules, which are stored in intracellular vesicles, have to be exposed on the cell surface. Moreover, for leukocyte attachment to ICAM-1-exposing ECs, the ICAM-1 molecules have to be arrayed in a certain pattern on the cell surface, a process that depends on the stiffness of the underlying matrix (9).…”
mentioning
confidence: 99%